Behavior of hybrid GFRP–perforated-steel tube-encased concrete column under uniaxial compression. (10th May 2016) - Huang, Liang; Yin, Peng; Yan, Libo; Kasal, Bohumil
Abstract: This study presents an experimental investigation on concrete confined by glass fiber reinforced polymer (GFRP) and perforated-steel tube subjected to uniaxial compression. The compressive behavior of this hybrid structure is compared with GFRP tube encased concrete and steel tube encased concrete. The three key experimental parameters were investigated: the layers of GFRP tube (1, 2, 3 and 4), the perforation diameter of porous steel tube (5 mm and 10 mm), and the grid form of perforated steel tube (axial type and helical type). The effects of these parameters on the failure mode, stress–strain relationship and ductility of the specimens were discussed. A simplified design model was proposed for the specimens and the predictions were in good agreement with the experimental results. In addition, the interactive function between steel and GFRP on the confined concrete was analyzed which considered an influence factor provided by these two confinement materials. This study showed that the hybrid GFRP–perforated steel tube exerts the full potential of these two materials, i.e. GFRP with its high tension strength enhanced the loading carrying capacity and the perforated-steel with its high elastoplasticity enhanced the deformation performance in hardening segment, softening branch and residual strength plateau of the concrete, respectively. This study therefore demonstrated that the combination of GFRP and perforated steel tubes is a new effective method to confine concrete.